Ultrafast coherent vibrational dynamics in dimethyl methylphosphonate radical cation1. Issue 7 (14th December 2017) - Ampadu Boateng, Derrick; Gutsev, Gennady L.; Jena, Puru; Tibbetts, Katharine Moore
Abstract : Coherent vibrational dynamics drive dissociation of dimethyl methylphosphonate (DMMP) radical cation. Abstract : Femtosecond pump–probe measurements of the nerve agent simulant dimethyl methylphosphonate (DMMP) demonstrate the preparation of a robust coherent vibrational state in the corresponding radical cation. The oscillations in the transient ion yields have a period of 45 fs (750 cm −1 ), which is at least 3 times faster than any previously observed oscillations in polyatomic radical cations. Use of 1200–1600 nm, as opposed to 800 nm, wavelengths for ionization increases the oscillation amplitude by a factor of 5 and doubles the number of visible oscillation periods from 6 to 12, indicating that an adiabatic ionization mechanism significantly enhances preparation of the coherent state. The coherent motion is assigned to a bending mode in DMMP + with frequency in the range of 742.2–754.7 cm −1 based on the results of DFT calculations. The observation of coherent nuclear dynamics in the dissociation of DMMP + suggests the potential utility of coherent control schemes for controlling the dissociation of DMMP and related molecules, which has important implications for developing detection and decontamination technologies for organophosphorus chemical warfare agents.